Islandness, Human Mobility and Left-Behindness: Insights from El Hierro, Canary Islands, Spain - Domínguez-Mujica, Josefina; Parreño-Castellano, Juan Manuel; Moreno-Medina, Claudio Jesús; Rodríguez-Rodríguez, Mercedes Á. (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2026)
The relationship between left-behindness and islandness is intricate and multifaceted. Small and peripheral islands are particularly susceptible to environmental challenges and economic downturns due to their limited resources for survival, which have historically shaped them as left-behind areas. However, while islands have long been viewed as places of departure, they also function as hubs for migrants, asylum seekers, tourists, and returnees, i.e., as spaces collectively modelled by human mobility. Therefore, islands are both peripheral and interconnected spaces, with relationality forming the core of islandness. The “relational isolation” is exemplified by the case of El Hierro in the Canary Islands, where human mobility may contribute to the mitigation of left-behindness. This analytical perspective is explored using statistical data that elucidates trends in human mobility, complemented by interviews with both migrants and stayers. These qualitative accounts offer critical insights into the migratory experience and its complex relationship with islandness.